2003
DOI: 10.1023/a:1026081824334
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Escherichia coli JM109 strains expressing either toluene dioxygenase from Pseudomonas putida F1 or biphenyl dioxygenase from Pseudomonas pseudoalcaligenes KF707 were examined for their ability to catalyze flavones. Biphenyl dioxygenase produced metabolites from flavone and 5,7-dihydroxyflavone which were not found in the control experiments. The absorption maxima of UV-visible spectra for the metabolites from flavone and 5,7-dihydroxyflavone were found at 337 and 348 nm respectively by using a photodiode array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For instance, the BPDO from Ps. furukawaii KF707 was demonstrated to catalyze the dihydroxylation of the flavone B-ring at positions C2′ and C3′ ( Kim et al, 2003 ). Interestingly, the study of Han et al (2005) reported that with flavanone, 6-hydroxyflavanone and 7-hydroxyflavanon, BPDO_KF707 acted as a monooxygenase introducing an epoxide functional group between C2′ and C3′ of the B-ring.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the BPDO from Ps. furukawaii KF707 was demonstrated to catalyze the dihydroxylation of the flavone B-ring at positions C2′ and C3′ ( Kim et al, 2003 ). Interestingly, the study of Han et al (2005) reported that with flavanone, 6-hydroxyflavanone and 7-hydroxyflavanon, BPDO_KF707 acted as a monooxygenase introducing an epoxide functional group between C2′ and C3′ of the B-ring.…”
Section: Discussionmentioning
confidence: 99%